(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Syndactyly is a condition in which two or more fingers are fused together, either congenital or secondary to trauma or hand burns. Syndactyly affects hand function, finger development, and aesthetic appearance. Surgical separation with webspace reconstruction is the standard treatment. This study was conducted at Children’s Hospital of Ho Chi Minh City to evaluate the outcomes of syndactyly release in young pediatric patients. Methods: Case series Results: A descriptive case series was performed from January 2025 to January 2026, including 11 patients (15 webspaces) who underwent syndactyly release. Both congenital and post-burn syndactyly cases were included. Webspace reconstruction was primarily performed using dorsal hand flaps (rectangular or bilobed flaps); full-thickness skin grafts were used when necessary. Outcomes were assessed at 3 months postoperatively based on webspace depth (Withey classification), finger range of motion (L. Frick criteria), complications, and parental satisfaction (Likert scale). Conclusions: Syndactyly release combined with dorsal hand flap webspace reconstruction in young children provides favorable functional and aesthetic outcomes with an acceptable complication rate. Appropriate flap design and slight overcorrection of web depth reduce the risk of web creep.